P‐205: Highly Sensitive Touch Panel Technology for Foldable AMOLED. Issue 1 (2nd June 2017) - Chen, Heng-Yin; Lu, Yi-Chuan; Chang, Kai-Ming; Yeh, Yung-Hui; Chen, Kuang-Jung
Abstract : This paper described a touch pattern design and de‐noise system integration for the foldable AMOLED display. We solved the interference caused by the small gap distance between touch sensor and the AMOLED cathode. A handheld foldable on‐cell touch AMOLED prototype was demonstrated. The signal‐to‐noise ratio (SNR) is 27.4dB and a high‐quality touch experience.